2021
DOI: 10.3390/agriculture11111070
|View full text |Cite
|
Sign up to set email alerts
|

Lime and Manure Amendment Improve Soil Fertility, Productivity and Nutrient Uptake of Rice-Mustard-Rice Cropping Pattern in an Acidic Terrace Soil

Abstract: Acid soil is an obstacle to agricultural development and a concern regarding food and environmental security. Therefore, a study was carried out for two consecutive years to see how lime and organic manure (OM) amendments affect yield and nutrient absorption in the Transplanted (T.) Aman–Mustard–Boro cropping pattern in an acidic terrace soil. With nine treatments and three replications, the experiment was set in a randomized complete block design. The treatments were applied to the first crop, T. Aman, with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
3
6
0
Order By: Relevance
“…Nitrogen is the most important yet limited nutrient among chemical fertilizers worldwide due to very low NUE due to gaseous losses such as denitrification, volatilization, and leaching from agricultural cropping systems [78,79]. Our results showed that the combined application of organic manure, inorganic fertilizer and dolomite significantly increased total crop yields (i.e., system productivity) of the cropping patterns (Tables 5 and 9), which is consistent with previous studies in acidic soil [7,24,25]. In the acidic soil of Nalitabari, Sherpur, Islam et al [7,24] reported that combined application of lime, organic amendment, and chemical fertilizer increased yield and nutrient uptake of the T. Aman-Maize-Fallow and Wheat-Mungbean-T. Aman cropping patterns.…”
Section: Effect Of Ipns On Crop Yield Nitrogen Uptake and Nitrogen Use Efficiencysupporting
confidence: 91%
See 3 more Smart Citations
“…Nitrogen is the most important yet limited nutrient among chemical fertilizers worldwide due to very low NUE due to gaseous losses such as denitrification, volatilization, and leaching from agricultural cropping systems [78,79]. Our results showed that the combined application of organic manure, inorganic fertilizer and dolomite significantly increased total crop yields (i.e., system productivity) of the cropping patterns (Tables 5 and 9), which is consistent with previous studies in acidic soil [7,24,25]. In the acidic soil of Nalitabari, Sherpur, Islam et al [7,24] reported that combined application of lime, organic amendment, and chemical fertilizer increased yield and nutrient uptake of the T. Aman-Maize-Fallow and Wheat-Mungbean-T. Aman cropping patterns.…”
Section: Effect Of Ipns On Crop Yield Nitrogen Uptake and Nitrogen Use Efficiencysupporting
confidence: 91%
“…Addition of organic and inorganic fertilizers significantly increased soil TN in acidic soil (Table 4), which aligns with Islam et al [7,24,25] and Van Chuong [67]. Previous research showed that the C:N ratio of the manure is essential for mineralization and the build-up of SOC and TN, and that a low C:N ratio boosts the mineralization process, resulting in increased soil TN [68,69].…”
Section: Effect Of Ipns On Soil Physicochemical Propertiessupporting
confidence: 86%
See 2 more Smart Citations
“…Suboptimal land is land that has low productivity and soil fertility so that it is not able to support plant growth optimally and is not economically profitable, either due to natural causes or due to human activities [4,5]. Therefore, as an effort to increase land productivity, it is necessary to improve soil fertility and essential nutrient cycles through the addition of organic matter, balanced fertilization, and/ or liming application [6,7]. Shahid and Al-Shankiti [8] stated that the organic matter addition can increase the efficiency of inorganic fertilizers through positive interactions in improving the quality of soil biological, chemical and physical properties.…”
Section: Introductionmentioning
confidence: 99%